Whiteness effectiveness in the use of activated charcoal: literature review (Research, Society and Development, 2022)
Objective: This study aimed to accomplish a literature review on the effect of activated carbon-based toothpastes on the dental structure. Materials and Methods: For data collection, searches were made in the main databases like Pubmed, LILACS, Scielo and Google academic, with the keywords: "Activated Carbon", "Dentifrices", "Tooth whitening". Articles published in national and international journals between the years 2001 to 2021 were selected. Results: Activated charcoal-based toothpastes are composed of abrasive particles that alter the surface of tooth enamel, by removing extrinsic pigments. The whitening agents, on the other hand, act on the intrinsic pigment of the tooth, by means of an oxidative reaction and it whitens the tooth effectively. Conclusion: The activated carbon-based dentifrices can promote dental color changes by extrinsic stains removal. However, the use of peroxide-based agents as teeth bleaching is the most indicated strategy, due to its effectiveness and biological safety.